Depositional Environments and Geochemical Assessments of the Bende Ameki Formation Potential as Petroleum Source Rocks in the Ogbunike Quarry, South-Eastern Nigeria - T. A., Olajubaje; S.O., Akande; J. A., Adeoye; O. A., Adekeye; C., Friedrich (European Scientific Journal, ESJ, 2018)
This paper focuses on investigating the paleoenvironments and hydrocarbon generation potentials of the outcropping Eocene Bende-Ameki Formation at Ogbunike quarry, Anambra Basin southeastern Nigeria, which is the Niger Delta Agbada Formation subsurface equivalent. The fine to coarse sandstones interbedded with parallel laminated grey, coaly shales, and bioturbated claystones were the dominant rock facies. The shales contain Ammobaculities, Ammontium, lenticulina, and Reophax benthic foraminifera of brackish to outer shelf environments. The rock sequence and biofacies associations indicate a fluvial, shoreface to delta environments. The marine and continental paleoenvironments are supported by the concentration and association of redox-sensitive trace elements such as vanadium and nickel of oxic to dysoxic paleoconditions. The twenty shales have a range of TOC from 0.39 - 8.81 wt% (mean 2.2 2 wt%), suggesting a good to very good source rocks. The organic richness is highest within the depth of 2 – 6 m across the quarry. Their genetic potential (S1+S2) ranges from 0.22 - 27.35 (mean 2.8 kgHC/ton) of rock, and hydrogen index from 26 to 292 mgHC/gTOC with a mean of 67.3 mgHC/gTOC. This, however, indicates dominance of Type III gas prone kerogen of terrestrial origin. The oxygenated water column characterized by the presence of benthonic scavengers may not preserve lipidenriched organic constituents of anoxic paleoenvironments which could account for the rare Type II oil and gas prone kerogen in the source rock. The thermal history inferred from the Tmax between 401°C - 424°C suggests that the source rocks are immature at the present stratigraphic level.